An Alliance of Trifolium repens—Rhizobium leguminosarum bv. trifolii—Mycorrhizal Fungi From an Old Zn-Pb-Cd Rich Waste Heap as a Promising Tripartite System for Phytostabilization of Metal Polluted Soils - Oleńska, Ewa; Małek, Wanda; Sujkowska-Rybkowska, Marzena; Szopa, Sebastian; Włostowski, Tadeusz; Aleksandrowicz, Olgierd; Swiecicka, Izabela; Wójcik, Małgorzata; Thijs, Sofie; Vangronsveld, Jaco (Frontiers in Microbiology, 2022)
The Bolesław waste heap in South Poland, with total soil Zn concentrations higher than 50,000 mg kg-1, 5,000 mg Pb kg-1, and 500 mg Cd kg-1, is a unique habitat for metallicolous plants such as Trifolium repens L. The purpose of this study was to characterize the association between T. repens and its microbial symbionts, i.e., Rhizobium leguminosarum bv. trifolii and mycorrhizal fungi and to evaluate its usefulness for phytostabilization of metal polluted soils. Rhizobia originating from the nutrient-poor waste heap area showed to be efficient in plant nodulation and nitrogen fixation. They demonstrated not only potential plant growth promotion traits in vitro but they also improved growth of T. repens plants to a similar extent as strains from a non-polluted reference area. Our results revealed that the adaptations of T. repens to high Zn-Pb-Cd concentrations are related to the storage of metals predominantly in the roots (excluder strategy), due to nodule apoplast modifications (i.e., thickening and suberization of cell walls, vacuolar storage), and the symbiosis with arbuscular mycorrhizal fungi of a substantial genetic diversity. As a result, the rhizobia-mycorrhizal fungi-T. repens association appears to be a promising tool for phytostabilization of Zn-Pb-Cd polluted soils.